2020
DOI: 10.5195/jmla.2020.607
|View full text |Cite
|
Sign up to set email alerts
|

“What’s happening over there?”: a study of the current state of services, challenges, and prospects in Nigerian medical libraries

Abstract: Objective: The authors examined the current state of service delivery, collections, and challenges in Nigerian medical libraries.Methods: We employed a descriptive mixed method research design using a cross-sectional quantitative survey of Nigerian medical librarians and qualitative interviews with heads of selected Nigerian medical libraries.Results: Respondents indicated that the US National Library of Medicine classification scheme is most commonly used to organize the resources of medical libraries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Research by Popoola et al identified a training need for librarians in Nigeria regarding EBP and systematic review (SR) [ 26 ]. Moreover, a 2017 survey to assess evidence synthesis capacity in Africa found that the top two reported hindrances to conducting evidence syntheses were “capacity, including experience, networking and collaboration” and “access to research literature and data” [ 27 ].…”
Section: The Workhop/smentioning
confidence: 99%
“…Research by Popoola et al identified a training need for librarians in Nigeria regarding EBP and systematic review (SR) [ 26 ]. Moreover, a 2017 survey to assess evidence synthesis capacity in Africa found that the top two reported hindrances to conducting evidence syntheses were “capacity, including experience, networking and collaboration” and “access to research literature and data” [ 27 ].…”
Section: The Workhop/smentioning
confidence: 99%